Lesung plus / Ahmad Naim Asfandi ... [et al.] - Asfandi, Ahmad Naim; Badlissah, Ameer Syafiq; Abd Halin, Mohamad Nur Naquib; Abdullah, Mohammad Faquarudin (2015)
he mortar and pestle are ancient tools used for cooking. Traditional pestle and mortar had been used since a long time ago. This equipment is widely used for grinding, crushing and pounding. Usually, this equipment is made of granite or wood. These kinds of materials give a unique taste to the ingredients put in the mortar. However, this utensils cause the user to become tired as it is manually operated. As the peoples get busy, they will find hard to use the traditional pestle and mortar due to lack of time. But, if they use the modern blender, they will not find the unique taste as the pestle and mortar can do. Therefore, Lesung Plus idea was generated to solve those problems. These utensils will become automatically operated because it is come with electrical motor. This Lesung Plus will have 3 main parts which is pestle and mortar, electrical motor and body frame. Its user can control the speed of the motor by using speed controller provided. Its body frame also covered with the transparent acrylic to increase its aesthetical value.